The mechanisms linking perceived stress to pilots’ safety attitudes: a chain mediation effect of job burnout and cognitive flexibility - Yanzeng, Zhao; Keyong, Zhu; Hongmin, Cai; Ziyu, Liu; Pengyu, Luo; Lijing, Wang (Frontiers in Public Health, 2024)
Introduction Pilots’ safety attitude is crucial for aviation safety. Current research shows a correlation between perceived stress and safety attitude, yet the mechanism underlying this association remains unclear. Against the backdrop of heightened attention to pilots’ stress, this study aims to thoroughly explore the inherent connection between pilot safety attitudes and their perceived stress, offering targeted insights into preventing and addressing safety attitude issues arising from pilot stress. Methods Through path analysis of questionnaire data from 106 civil aviation pilots in China, this study systematically investigates the roles of job burnout and cognitive flexibility in the relationship between perceived stress and safety attitude. The study reveals the chain-mediated mechanism of these two factors. Results The results demonstrate a significantly negative correlation between pilots’ perceived stress and safety attitude, with cognitive flexibility and job burnout fully mediating this relationship, and cognitive flexibility affecting job burnout. A detailed analysis of the three dimensions of job burnout reveals varying impacts of emotional exhaustion, depersonalization, and reduced personal accomplishment on the aforementioned path. The research model exhibits a good fit (GFI=0.902), providing new theoretical perspectives on the association between pilots’ perceived stress and safety attitude. Discussion The findings offer practical implications for improving pilots’ safety attitude by proposing targeted measures to alleviate the adverse impacts of perceived stress on safety attitude, thereby promoting aviation safety.